Tie-Line Bias Control for Frequency Deviation in the Presence of System Uncertainties with WTG and BESS: A Robust Control Approach - Singh S.; Verma M.K. (My University, 2025)
In stand-alone mode, an AC power system such as microgrid can experience large frequency deviations arising due to RES (Renewable Energy Sources) power fluctuations. In this paper, a robust Proportional-Integral-Derivative (PID) tuner-based controller is proposed for mitigating the frequency transients arising from the variation in load and renewable energy resources power output. Conventional PID controllers are incapable of handling the system uncertainties. This work tries to develop robust control strategies for both the battery and conventional generation systems, with controllers designed to significantly reduce frequency variation, despite variable loads in the microgrid and the incorporation of a Wind Turbine Generator (WTG) source. Controllers are designed to cope with load transients, WTG output fluctuations and model uncertainties. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.